After form. The credibility thesis meets property theory. (December 2018) - Davy, Benjamin
Abstract: According to the credibility thesis (Ho, 2014 and 2016), property in land is determined by its functions. The form of property would follow its functions. But what type of form follows the functions of property? The article considers four meanings of the concept of 'form of property:' property in the Blackstonian sense as a mere shell for ownership (and its counterpart, property as social function); the sources of property law ( fontes iuris ) in international and domestic law; property as a highly formalized right in a legal system well-ordered by land cadastres and land registers (and its counterpart, informal land rights); and property as a standardized 'bundle of rights' (and its counterpart, polyrational or bespoke property). Since land rights, fulfilling their desired function, can be credible without full formalization or standardization, land policy must not consider dichotomies (such as 'formal' versus 'informal'), but degrees of (in)formality or credibility.